Manajemen Waktu Pada Pekerjaan Arsitektur Proyek Pembangunan Gedung Yayasan Pelita Ilmu Insani - Windi; Aguswin, Ahmad; Akromusyuhada, Akhmad (SAFE-Network, 2024)
The success or failure of a project can be influenced by the lack of planning of project activities, and the supervision carried out is ineffective and has an impact on the project running inefficiently. Then, it will result in delays and a decrease in the quality of work and have an impact on swelling the project budget. Project management is needed in order to manage projects starting from implementation to the end of a project. This research uses a case study on the Pelita Ilmu Foundation Building Construction Project, especially architectural work. This building is located on Jl. Rawa Kuda, Kp. Rawa Kuda RT/RW 004/002 Karangharum, Kedungwaringin District, Bekasi Regency, West Java 17540 [1]. The S curve is used to find out how long a project takes to complete. The aim of this research is to determine time efficiency in terms of the S Curve graph. The results of time management analysis using the S Curve on the graph showed that the realization of time delays was not in accordance with the plan.